Maintaining the Social Environment: Urgency and Principles in Maqasid Al-Shariah - Abdulloh Munir; Kusnadi, Kusnadi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The persistent challenges within the social environment remain a critical area of inquiry, particularly given the intertwined relationship between humanity and the environment that necessitates protection. Integrating Maqasid Al-Shariah with social environmental issues is essential for developing a comprehensive framework for safeguarding this environment (hifz al-bi'ah al-ijtima'iyyah). This study attempts to delineate the scope of maintaining the social environment and to identify actionable steps that can be synergized between society, government, and the guiding principles of Maqasid Al-Shariah. Utilizing a literature-based research methodology, this study employs analytical techniques in data reduction, data display, and conclusion drawing from primary references on Maqasid Al-Shariah and selective studies on the social environment. The findings reveal the critical importance of contextualizing Qur'anic and Hadith arguments related to the social environment, emphasizing care, protection, and the development of both natural and human resources. This approach leverages the inherent qualities of human beings as God's creations, including their intellect and spirit, to promote collective benefit. Novel contributions of this research include the application of Islamic values to control social and environmental degradation, an understanding of human nature's interaction with the social environment, and the implementation of amar ma'ruf nahi munkar within this context, supported by government intervention. The implications of this study underscore the need for a comprehensive and mutually agreed-upon concept of environmental protection, aligned with Islamic values, between government and society.